Measurement of CP asymmetry in B0s→Dminus plusK± decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; et al. (Journal of high energy physics, 2018)
We report the measurements of the CP -violating parameters in B s 0 → D s ∓ K± decays observed in pp collisions, using a data set corresponding to an integrated luminosity of 3.0 fb−1 recorded with the LHCb detector. We measure Cf = 0.73 ± 0.14 ± 0.05, A f ΔΓ = 0.39 ± 0.28 ± 0.15, AΔΓf¯¯¯=0.31±0.28±0.15Af¯ΔΓ=0.31±0.28±0.15 A_{\overline{f}}^{\varDelta \varGamma }=0.31± 0.28± 0.15 , Sf = −0.52 ± 0.20 ± 0.07, Sf¯¯¯=−0.49±0.20±0.07Sf¯=−0.49±0.20±0.07 S_{\overline{f}}=-0.49± 0.20± 0.07 , where the uncertainties are statistical and systematic, respectively. These parameters are used together with the world-average value of the B s 0 mixing phase, −2βs, to obtain a measurement of the CKM angle γ from B s 0 → D s ∓ K± decays, yielding γ = (128 − 22 + 17 )° modulo 180°, where the uncertainty contains both statistical and systematic contributions. This corresponds to 3.8 σ evidence for CP violation in the interference between decay and decay after mixing. Open image in new window
Im Titel werden "0", "minus plus" und "plus minus" hochgestellt
Gesehen am 22.05.2019
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D.Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, S. Esen, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecná, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]